Strong meat to digest - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Farm Animal Metabolism and Nutrition Edited by J P F D Mello, The Scottish Agricultural College, CABI, May 2000. 448 pp. ISBN 0 85199 378 8 £35 E 57.15